Plasma cortisol levels in captive wild felines after chemical restraint - Nogueira, Guilherme de Paula [UNESP]; Silva, J. C. R. [UNESP] (Associação Brasileira de Divulgação Científica (ABRADIC), 1997)
Eight Panthera onca (Po), 13 Felis concolor (Fc), 7 Felis yagouaroundi (Fy), 7 Felis tigrina (Ft) and 5 Felis pardalis (Fp) specimens from São Paulo State zoos were used. All animals were restrained with darts containing 10 mg/kg ketamine and 1 mg/kg xylazine. Venous blood samples were collected as soon as possible (within 15-20 min) and serum was frozen until the time for cortisol quantification. Cortisol was determined using a solid phase radioimmunoassay with an intra-assay coefficient of 8.51%. Data were analyzed statistically by the Kruskal-Wallis test, followed by Dunn's multiple comparisons test, and the one-sample t-test, with the level of significance set at P<0.05. Data are reported as means ± SEM. Cortisol levels differed among the captive felines: Po = 166 ± 33a, Fc = 670 ± 118b, Fy = 480 ± 83b, Ft = 237 ± 42ab, Fp = 97 ± 12a nmol/l (values followed by different superscript letters were significantly different (P<0.001)). Since most of the veterinary procedures on these species involve chemical restraint, these results show the necessity of preventive measures in order to minimize the effect of restraint stress on more susceptible species
Keywords: wild felines; plasma cortisol; captive felines